2018
DOI: 10.1038/s41598-018-23178-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Esophageal Eosinophilia in a Pediatric Population from Central Brazil

Abstract: Here we report a retrospective cross-sectional study on Esophageal eosinophilia (EsEo) frequency in Brazil, for 2, 425 pediatric patients with symptoms associated with gastroesophageal diseases in 2012. EsEo is defined by ≥15 eosinophils per high power field (400x) and confirmed through histological analyses of esophageal biopsies. Overall, 126 patients had EsEo equating to a frequency of 5.2%. There was a significant difference between the endoscopic features of patients with EsEo, where 10.7% had erosive eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…In accordance with previous studies, the distribution of the eos in our study showed a gradual increase across the proximal segments of the GI tract, from the esophagus to the ileum, followed by a subsequent gradual decrease from the first segments of the colon to the rectum [ 3 , 4 ]. The range of eos/hpf in esophageal biopsies in our study was consistent with the findings of previous studies that reported up to 6 eos/hpf in healthy esophageal mucosa of children between 7-15 years of age [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies, the distribution of the eos in our study showed a gradual increase across the proximal segments of the GI tract, from the esophagus to the ileum, followed by a subsequent gradual decrease from the first segments of the colon to the rectum [ 3 , 4 ]. The range of eos/hpf in esophageal biopsies in our study was consistent with the findings of previous studies that reported up to 6 eos/hpf in healthy esophageal mucosa of children between 7-15 years of age [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly enough, performing a specific genetic panel for EoE demonstrated that, at a genetic level, EoE prevalence is lower in Hispanic patients compared to Caucasians 5 . Brazil reported an EoE incidence in children similar to North America (5%), with a preference toward males of 2.5:1 6 .…”
Section: Introduction and Epidemiologymentioning
confidence: 90%